2010
DOI: 10.1213/ane.0b013e3181cb6791
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Double-Blind Comparison of Ultrasound-Guided Axillary Brachial Plexus Blocks Using 2 Versus 4 Injections

Abstract: An ultrasound-guided 2-injection axillary block may be as effective as, and more time efficient than, a 4-injection technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 4 publications
2
47
1
3
Order By: Relevance
“…supraclavicular [7,26,28,33,36,37,41]; and one trial compared the three approaches [6]. Eleven trials compared one with multiple injections: for the axillary approach [22,23,30,34,40]; for the infraclavicular approach [27,29,32]; and for the supraclavicular approach [9][10][11]. Five authors provided data when requested [7,10,26,27,32].…”
Section: Resultsmentioning
confidence: 99%
“…supraclavicular [7,26,28,33,36,37,41]; and one trial compared the three approaches [6]. Eleven trials compared one with multiple injections: for the axillary approach [22,23,30,34,40]; for the infraclavicular approach [27,29,32]; and for the supraclavicular approach [9][10][11]. Five authors provided data when requested [7,10,26,27,32].…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies have shown that two injections (one around the musculocutaneous nerve and another posterior to the axillary artery) provide an equivalent success rate than the identification and injection of each of the four major nerves. 30,31 In addition to reducing the time needed to perform the block, this technique requires the operator to identify only the musculocutaneous nerve, which greatly simplifies the technique (Fig. 9) (Videos 4a and 4b, available as ESM).…”
Section: Axillary Approachmentioning
confidence: 99%
“…Deux études récentes ont démontré que deux injections (une autour du nerf musculocutané et une seconde en postérieur de l'artère axillaire) procurent un aussi bon taux de succès que l'identification et l'injection de chacun des quatre nerfs majeurs. 30,31 En plus de réduire la durée de réalisation du bloc, cette technique nécessite uniquement l'identification du nerf musculocutané, simplifiant grandement la technique (Fig. 9), (Vidéos 4a et 4b, disponibles en matériel électronique supplémentaire).…”
Section: Approche Infraclaviculaireunclassified
“…The mean time required for these manipulations and the deposition of an anaesthetic agent during ultrasound-guided axillary block ranges from app. eight minutes to more than 15 minutes (Table 3) [6,8,20,21]. In this case, the time required for preparation, setup of the ultrasound machine and protection of a transducer.…”
Section: Time Of Block and Onset And Duration Of Analgesiamentioning
confidence: 99%